2022
DOI: 10.1039/d2py00061j
|View full text |Cite
|
Sign up to set email alerts
|

White light-induced AIEgen polyurethane films containing Schiff base copper(ii) complexes for synergistic chemo/photodynamic antibacterial therapy

Abstract: To solve the problem of bacteria resistance caused by the overuse of antibiotics, we successfully prepared a sort of polyurethane (PU) composite film with dual antibacterial effects. These films can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…An antibacterial film coating on the surface of object can greatly improve the bactericidal function and application of materials. [61][62][63] In 2020, Yang et al reported an AIE-active 2D biopolymer film system, called DSAI@PTL monomer, from the cationic antimicrobial AIEgen (DSAI), phase-transited lysozyme (PTL) and tris(2-carboxyethyl)phosphine (TCEP) (Figure 7a). [63] The DSAI@PTL nanofilm showed an extremely high killing selectivity (99%) to Gram-negative bacteria, Gram-positive bacteria, and fungus (Figure 7b), but with a low cytotoxicity to mammalian cells, demonstrating its safe for practical usage.…”
Section: Film and Textilementioning
confidence: 99%
“…An antibacterial film coating on the surface of object can greatly improve the bactericidal function and application of materials. [61][62][63] In 2020, Yang et al reported an AIE-active 2D biopolymer film system, called DSAI@PTL monomer, from the cationic antimicrobial AIEgen (DSAI), phase-transited lysozyme (PTL) and tris(2-carboxyethyl)phosphine (TCEP) (Figure 7a). [63] The DSAI@PTL nanofilm showed an extremely high killing selectivity (99%) to Gram-negative bacteria, Gram-positive bacteria, and fungus (Figure 7b), but with a low cytotoxicity to mammalian cells, demonstrating its safe for practical usage.…”
Section: Film and Textilementioning
confidence: 99%
“…[13][14][15][16] Physical modification is often suitable for inorganic antibacterial agents, such as silver, copper, and zinc. [17][18][19] However, how to maintain stable antibacterial activity, avoid leakage of antibacterial agents, and biological toxicity caused by leakage still needs a lot of exploration and solution. Thus, the introduction of an antibacterial agent or antibacterial group into the WPU molecular chain by chemical bonding to impart antibacterial activity is a better way to solve the above problems.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Among them, the commonly used additive antibacterial agents such as silver, copper, zinc oxide, and so forth have practical problems including poor compatibility with substrates, environmental migration contamination, reduced antibacterial persistence, and toxicity. [12][13][14] Therefore, introducing a stable covalent bond between WPU and the antibacterial functional groups may be a better alternative to avoid the above problems. For instance, WPU with good biocompatibility and antibacterial properties was prepared using L-lysine-derived quaternary ammonium salt (QAs) diamine as a chain extender and ethylene glycol diglycidyl ether as a cross-linking agent to improve the antibacterial durability of the materials by chemical cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…So far, antibacterial agents have been introduced into WPU by physical addition and covalent binding to induce antibacterial effects 8–11 . Among them, the commonly used additive antibacterial agents such as silver, copper, zinc oxide, and so forth have practical problems including poor compatibility with substrates, environmental migration contamination, reduced antibacterial persistence, and toxicity 12–14 . Therefore, introducing a stable covalent bond between WPU and the antibacterial functional groups may be a better alternative to avoid the above problems.…”
Section: Introductionmentioning
confidence: 99%